Promoting Mental Health During the COVID-19 Pandemic: A Hybrid, Innovative Approach in Malaysia - Mat Ruzlin, Aimi Nadira; Chen, Xin Wee; Yunus, Raudah Mohd; Samsudin, Ely Zarina; Selamat, Mohamad Ikhsan; Ismail, Zaliha (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic has had monumental effects on the mental health of populations worldwide. Previous research indicated that programs and interventions using social networks can play a positive role in promoting mental health. Nevertheless, current evidence is largely derived from high-income regions, reflecting an urgent need for more studies in low- and middle-income settings. Objectives: This paper aims to (a) describe the potential value of a hybrid health carnival in promoting mental health and increasing access to screening services; (b) assess the level of community engagement with the digital platform. Methods: A mental health carnival was conducted with the theme of “Mind Your Mental Health” (Cakna Kesihatan Mental) in conjunction with the World Mental Health Day in Malaysia. This was a hybrid carnival that combined elements of face-to-face interactions and virtual learning. Free online therapy sessions were offered to high-risk groups identified during the screening process. Social media metrics were utilized to report the levels of community engagement and participants completed pre-and post-assessments to measure the program's impact on their knowledge. Results: The carnival was attended by 515 participants (78.8% virtual participants). Social media metrics reported more than 5,585 reaches on Facebook for all the activities held throughout the event. Results from pre-and post-assessments showed significant improvement in the mean knowledge scores (p < 0.05). Conclusion: This digital approach will continue to evolve by releasing new features and tools as a new frontier for high-risk populations and all individuals seeking mental health support and treatment.